De-Europeanisation in European foreign policy-making: assessing an exploratory research agenda. Issue 5 (4th July 2021) - Smith, Michael
ABSTRACT: This Conclusion poses a number of cross-cutting questions, and explores the ways in which the Special Issue has addressed them. The questions are: (1) Is de-Europeanisation in European foreign policy-making simply an 'internal' process? (2) Is de-Europeanisation a tactic or a trend? (3) Is de-Europeanisation in European foreign policy-making just 'politics'? (4) Is de-Europeanisation about capacity, or about legitimacy? (5) How does de-Europeanisation relate to the potential costs and risks of European foreign policy? (6) Is de-Europeanisation a one-way street? In addressing these issues, the article identifies a number of potential areas for further research relating to the forms, processes and implications of de-Europeanisation.